The Church in Antioch in the First Century C.E - Draper, Jonathan A. 1949- (2005)
In this book, Michelle Slee courageously takes on the scholarly consensus regarding what may be described as the “storm centre” of the study of Christian origins, namely the origin and growth of the church in Antioch and the incident between Paul and the “judaizers” over table fellowship.
Keywords: Rezension